The Role of Personality, Conspiracy Mentality, REBT Irrational Beliefs, and Adult Attachment in COVID-19 Related Health Behaviors - Stanković, Sanda; Lazarević, Ljiljana B.; Knežević, Goran (Studia Psychologica, 2022)
There is evidence that different types of irrational thinking and beliefs are significant predictors of questionable and maladaptive COVID-19 related health practices. In this study, we investigated the role of two under-researched types of irrational thinking, more typical for a clinical setting: irrational beliefs defined in Rational Emotive Behavior Therapy (REBT) and attachment anxiety and avoidance. We investigated whether REBT irrational beliefs, attachment dimensions, and conspiracy mentality mediated the relationship between personality traits, on the one side, and COVID-19 health behaviors, on the other. We proposed that HEXACO personality traits, and especially Disintegration (proneness to psychotic-like experiences) predicted irrational thinking and beliefs, which in turn predicted higher susceptibility to questionable health practices. Structural equation modeling on a sample of 287 participants from the general population, showed that Disintegration was related to REBT irrational beliefs, attachment dimensions, and conspiracy mentality, highlighting the important effect of Disintegration on irrational thinking and beliefs. Conspiracy mentality mediated the effects of Disintegration to low adherence to recommended health behaviors – RHB, and greater use of pseudoscientific practices – PSP. Attachment anxiety mediated the relationship between high Disintegration, high Emotionality (E), and low Honesty (H), and lower adherence to RHB. REBT irrational beliefs and attachment avoidance did not mediate the relationship between personality traits and COVID-19 health behaviors.